The Effect of Arab Environment on the Artist's Works August Renoir: The Effect of Arab Environment on the Artist's Works August Renoir (Journal of the College of Education for Women, 2019)
Abstract:This study is considerated one of many Studies above the standing ofthe Islamic Arab nation which was chosen by God from other nations all overthe world . Some of these nations used to come to the Arab nation to takewhatever useful for them from the beginning of history till now . Theresearcher deals in this study with a French artist who is well-know asAugust Renoir . He traveled to Algeria and lived there . He wasinfluenced by the Islamic culture.The study include. from chapter . chapter one deals with the framework ofprogramming (out line ) . Chapter two deals with the theoretical framework .It includes five sections. Deals with the Islamic drawings(Arabesque) . sectionthree deals with on introduction of the important schools and their relationwith the Islamic Arab culture . section four deals with the school ofimpression . Section five deals with August Renoir's life in the ArabHomeland . Chapter three deals with the procedures and analysis of importantsamples related to (August), the French Artist's work . Chapter four dealswith the conclusion and results . the referencesend the study .